Vikten av kognitiva tumregler vid utvärdering av källors trovärdighet - Sundberg, Emma (2016)
This thesis has examined which cognitive heuristics are most often used in source evaluation tasks, depending on the respondents own estimated ability to evaluate a source. A survey based on Metzger and Flanagins (2013) cognitive heuristics, was sent to 1000 programme students at Luleå University of Technology, out of which 226 replies were received. The data was analysed with multiple linear regression analysis and the results show a correlation between the participants own estimation of their ability to evaluate the credibility of sources and the consistency heuristic, and a negative correlation with the self-confirmation heuristic. Validerat; 20160824 (global_studentproject_submitter)